Masyarakat moden dan dunia pendidikan - Hashim, Rosnani (Yayasan Takmir, 1992)
Modernization, the product of western colonization as many would regard has left indelible mark upon people's culture and thought. Perhaps the most outstanding of all is that the phenomenon of alienation. Man become alienated from his cultural and religious norms and life as a result of being subservient to the dictates of modern life. There are other elements brought about modernization, namely extreme bureaucratization and obsession to technology. These have aggravated the phenomenon of alienation. Man has become alienated from his God, his society, his environment and finally his ownself. This is perhaps the greatest challenge that the world of education has to address.